Ultrasound reference values for the calcaneus of children and adolescents at moderate altitudes in Peru - Rossana Gómez-Campos; Jose Sulla-Torres; Cynthia Lee Andruske; Luis Felipe Castelli Correia de Campos; Cristian Luarte-Rocha; Wilbert Cossio-Bolaños; Marco Antonio Cossio-Bolaños (Elsevier, 2021)
Objective: a) Establish reference values for bone parameters by using the speed of sound (SOS, m/s) of broadband ultrasound attenuation (BUA, dB/MHz) and establish a bone quality index (BQI = αSOS + βBUA) for children and adolescents living in a region of moderate altitude, b) compare bone parameters with an international standard (with different ethnic, socio-economic, and lifestyle backgrounds) by using ultrasound of the calcaneus (heel bone) (QUS). Methods: A descriptive cross-sectional study was carried out with children and adolescents between the ages of 6.0 and 16.9 years old. The sample was selected randomly. A total of 1322 subjects were studied. Weight, height, and bone parameters, using ultrasound of the calcaneus, were evaluated SOS, BUA, and BQI. Body Mass Index BMI was calculated. Results: The average age of males was 11.44 ± 0.35 years old, and for females, it was 11.43 ± 0.35 years old. The students in this research showed slightly higher values of SOS, BUA, and BQI for both sexes when compared with the international reference (the 50th percentile). Percentiles were generated (P3, P10, P25, P50, P75, P90, and P97) using the LMS method [median (M), standard deviation (S), and power of the Box-Cox transformation (L)] by age and sex. Conclusion: The students living at a moderate altitude showed slightly higher values in bone parameters in relation to the international reference. This pattern depicted a population with a better state of bone health. The proposed percentiles may be used to categorize adequate to at risk bone parameters based on age and sex.